STRATEGI IMPLEMENTASI KEBIJAKAN DINAS KESEHATAN KABUPATEN BANDUNG BARAT DALAM INTERVENSI STUNTING PADA MASA PANDEMI COVID-19 - Fitri Aditri (2021)
The government has a target of reducing stunting to 14% by 2024. However, the COVID-19 pandemic has the potential to disrupt the government's focus in reducing stunting, including the West Bandung District Health Office, whose area is the focus location for stunting since 2018. This research aims to explore policy implementation strategies West Bandung District Health Office in stunting intervention during the COVID-19 pandemic. The method used in this research is descriptive qualitative with a case study approach. The research informants were 4 people who were officials in the work area of the West Bandung District Health Office and including the inclusion criteria. Data were collected by in-depth interviews, documentation, and triangulation. After processing and analyzing the data, the following results were obtained: The strategy for implementing the policies of the West Bandung District Health Office in stunting interventions, especially specific nutrition interventions during the COVID-19 pandemic, including through a role-sharing approach, making more use of digital media, every activity carried out in accordance with health protocols, sweeping Posyandu, using priority strategies to streamline the budget and synergize the COVID-19 prevention program with stunting prevention. Despite having a special strategy, the increase in the prevalence of stunting during the COVID-19 pandemic in West Bandung Regency is unavoidable.